TINJAUAN PENERAPAN AKTIVA TETAP BERDASARKAN PSAK NO. 16 PADA PT. EKA SARI LORENA TRANSPORT TAHUN 2012-2013 - ., Jeffry (STIE Binaniaga, 2013)
Role of fixed assets both service companies and manufacturing companies are basically the same, ie fixed assets have a very important role as a support for companies in doing the activities and operations of the company. To keep the fixed assets can be used in accordance with its function, then the asset must remain in good condition. Therefore, it is important for companies to carry out the management of fixed assets. Because of the role and function of the fixed assets is crucial to achieve the company's goal has been determined. Fixed assets have limited use of the age limit, except land. Sometimes the fixed assets needed repairs caused by damage and worn out, so it can extend the useful life, increase production capacity and improve the quality of production of the assets concerned. PT. Eka Sari Lorena Transport only classifying fixed assets based on the depreciable fixed assets such as office equipment, inventory workshop, office vehicles, buses and construction operations. Initial recognition of assets based on data obtained PT. Eka Sari Lorena Transport in acquiring fixed assets carried out by way of a cash purchase, purchase on credit, and build it yourself. There are expenses that companies face during the period of use of the fixed assets in order to meet the needs of companies that repair and maintenance, replacement, and addition. Usually load a small amount included as part of the operating expenses of the current year, while load large amounts capitalized into the asset as an addition to the acquisition price. PT. Eka Sari Lorena Transport perform depreciation on all types of fixed assets, except land, there are two factors that cause a decrease in the ability of depreciation of fixed assets, namely the physical or functional depreciation, the company conducts depreciation using the straight-line method based on the estimated useful life and the economic life of termination to all fixed assets conducted since the end of its useful life, damaged, less useful for companies should be eliminated or released by PT. Eka Sari Lorena Transport. Disclosure of fixed assets in the financial statements of the company using the straight-line method of depreciation in the calculation of all types of fixed assets, fixed assets valuation basis disclosed at acquisition cost, the company revealed that the fixed assets are recorded at cost less accumulated depreciation and depreciation burden reported in the income statement as an expense Suitability fixed assets accounting firm with SFAS No. 16 at initial recognition fixed assets, expenses for the use, termination of fixed assets, depreciation of fixed assets, as well as the disclosures in the financial statements do not fully implemented by the company.Keyword: Fixed Asset